2012
DOI: 10.2147/cia.s34034
|View full text |Cite
|
Sign up to set email alerts
|

Modulating testosterone pathway: a new strategy to tackle male skin aging?

Abstract: In men, the level of testosterone decreases with age. At the skin level, the result is observed as a decrease in density and in a lower elasticity. Identifying compounds that are able to increase the level of testosterone appears to be an attractive strategy to develop new antiaging bioactive ingredients for men. Reverse pharmacognosy was successfully applied to identify new natural compounds able to modulate testosterone levels. Among several in silico hits, honokiol was retained as a candidate as it has the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…These results are in accordance with research conducted by Latreille et al, 2012 which found 1655 men and 1264 women that there was no significant relationship between photoaging and gender [13]. In men, moisture, skin elasticity, and skin thickness are influenced by the hormone testosterone, while in women the most important role in regulating skin physiology, targeting keratocytes, fibroblasts, melanocytes, hair follicles, and sebaceous glands as well as increasing angiogenesis, wound healing, and an immune response is the hormone estrogen [14,15].…”
Section: Discussionmentioning
confidence: 94%
“…These results are in accordance with research conducted by Latreille et al, 2012 which found 1655 men and 1264 women that there was no significant relationship between photoaging and gender [13]. In men, moisture, skin elasticity, and skin thickness are influenced by the hormone testosterone, while in women the most important role in regulating skin physiology, targeting keratocytes, fibroblasts, melanocytes, hair follicles, and sebaceous glands as well as increasing angiogenesis, wound healing, and an immune response is the hormone estrogen [14,15].…”
Section: Discussionmentioning
confidence: 94%
“…Honokiol, the molecular constituent of Magnolia officinalis Rehder et Wilson or Magnolia grandiflora L., is a Chinese medicinal plant [82]. Its pharmacological effects include antiinflammatory, antithrombotic, antiarrhythmic, antioxidative, central depressant, muscle relaxant, and anxiolytic effects [82].…”
Section: Discussionmentioning
confidence: 99%
“…Honokiol, the molecular constituent of Magnolia officinalis Rehder et Wilson or Magnolia grandiflora L., is a Chinese medicinal plant [82]. Its pharmacological effects include antiinflammatory, antithrombotic, antiarrhythmic, antioxidative, central depressant, muscle relaxant, and anxiolytic effects [82]. In the endocrine system, honokiol activates the ERK/cfos signaling pathway, increases levels [83], increases the mRNA expression of glucocorticoid receptors in the hippocampus [84], improves insulin resistance in type 2 diabetic db/db mice [85], and inhibits 5-alpha-reductase type 1, modulating testosterone levels in vitro [82].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) Generated during oxidative cell metabolism, mostly at mitochondria [14,15]; DNA damage Telomer shortening, gene loss, decreased DNA methylation and phosphorylation reaction, decreased DNA repair, oncogene and tumor suppressor gene deregulation [16,17]. Hormonal changes Estrogen decline during menopause, testosterone decline both in men and women [18,19].…”
Section: Factors and Mechanismsmentioning
confidence: 99%